ChemInform Abstract: Synthesis and Characterization of Alkyl‐Imidazolium‐Based Periodic Mesoporous Organosilicas: A Versatile Host for the Immobilization of Perruthenate (RuO4‐) in the Aerobic Oxidation of Alcohols. Issue 13 (18th March 2013) - Karimi, Babak; Elhamifar, Dawood; Yari, Omolbanin; Khorasani, Mojtaba; Vali, Hojatollah; Clark, James H.; Hunt, Andrew J.
Abstract The catalyst can be recycled and used in at least four runs with only a slight loss in activity.